Comparative Legal Analysis of Stunning Methods in Halal Animal Slaughter Between Muslim-Majority and Muslim-Minority Countries - Kurniawan, Adityo Wiwit; Alam, Azhar; Yuspin, Wardah; Rizka (NAJAHA, 2025)
The global halal industry is growing rapidly, driven by the growth of the Muslim population and increasing demand for products that meet sharia standards and animal welfare. One of the central issues in this industry is the method of stunning in the slaughter of halal animals, which has sparked debate between sharia principles and modern animal welfare standards. This study conducts a comparative legal analysis of stunning methods in halal animal slaughter between majority Muslim countries (Indonesia, Malaysia, and Saudi Arabia) and minority Muslim countries (the United Kingdom, the United States, and Australia). The results show that Muslim-majority countries generally accept stunning methods with strict conditions in accordance with Sharia principles, such as MUI Fatwa No. 12/2009 and Malaysian Halal standards, which permit stunning as long as the animal remains alive during slaughter. Conversely, Muslim-minority countries require stunning to meet international animal welfare standards, although they grant exceptions for ritual halal slaughter in the interest of religious freedom. The study also revealed differences in fatwas, such as Aceh's ban on all forms of stunning, which is deemed contrary to the principle of ihsan and increases animal suffering. These regulatory differences reflect the challenges of harmonizing Sharia principles with modern animal welfare standards and global market demands. Therefore, interdisciplinary dialogue between religious scholars, scientists, and halal industry stakeholders is essential to develop evidence-based stunning standards, operator training, and consumer education to support the sustainable and globally trusted modernization of the halal industry.